Internal mammary node irradiation in early breast cancer – target coverage and implications on dose to organs at risk - Lovisa Berg; Jeanette Sporre; Elisabeth Kjellén; Sofie Ceberg; Elinore Wieslander; Sara Alkner (Acta Oncologica)
Purpose: Indications for radiotherapy (RT) of the internal mammary nodes (IMN) in early breast cancer vary between countries. While studies indicate benefits, IMN RT increases the dose to the heart and lungs, and the risk-benefit ratio of this treatment is debated. This study investigates how IMN RT affects dose to organs at risk (OAR) and pneumonitis incidence in a clinical setting.